Establishment of mammary gland model in vitro: culture and evaluation of a yak mammary epithelial cell line. - Mei Fu; Yabing Chen; Xianrong Xiong; Daoliang Lan; Jian Li (PLoS ONE, 2014)
This study aimed to establish yak mammary epithelial cells (YMECs) for an in vitro model of yak mammary gland biology. The primary culture of YMECs was obtained from mammary gland tissues of lactating yak and then characterized using immunocytochemistry, RT-PCR, and western blot analysis. Whether foreign genes could be transfected into the YMECs were examined by transfecting the EGFP gene into the cells. Finally, the effect of Staphylococcus aureus infection on YMECs was determined. The established YMECs retained the mammary epithelial cell characteristics. A spontaneously immortalized yak mammary epithelial cell line was established and could be continuously subcultured for more than 60 passages without senescence. The EGFP gene was successfully transferred into the YMECs, and the transfected cells could be maintained for a long duration in the culture by continuous subculturing. The cells expressed more antimicrobial peptides upon S.aureus invasion. Therefore, the established cell line could be considered a model system to understand yak mammary gland biology.